2019
DOI: 10.1002/brb3.1260
|View full text |Cite
|
Sign up to set email alerts
|

OralLactobacillus reuteriLR06 orBifidobacteriumBL5b supplement do not produce analgesic effects on neuropathic and inflammatory pain in rats

Abstract: Background Previous studies have reported that certain bacteria exert visceral antinociceptive activity in visceral pain and may also help to relieve neuropathic and inflammatory pain. Objective: The aim of this study was to explore the analgesic effect of Lactobacillus reuteri LR06 (LR06) or Bifidobacterium BL5b (BL5b) in chronic pain in vivo. Design Rats were randomly assigned into four groups: sham, Chronic Constriction Injury (CCI)/Complete Freund's Adjuvant (CFA) + control, CCI/CFA + LR06, and CCI/CFA + B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Huang et al [42] attempted to treat neuropathic pain in rats with oral supplementation of probiotics (i.e., Lactobacillus reuteri LR06 or Bifidobacterium BL5b), but failed. Along with the reasons provided by Huang et al [42], we speculate that the treatment failed because key microbes in the rats with neuropathic pain were influenced by and cooperated with the probiotics for survival, and these attenuated the analgesic effects of the probiotics. Interestingly, Staphylococcus, the key microbe in the SNI group, influenced Lactobacillus through cooperative interactions in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al [42] attempted to treat neuropathic pain in rats with oral supplementation of probiotics (i.e., Lactobacillus reuteri LR06 or Bifidobacterium BL5b), but failed. Along with the reasons provided by Huang et al [42], we speculate that the treatment failed because key microbes in the rats with neuropathic pain were influenced by and cooperated with the probiotics for survival, and these attenuated the analgesic effects of the probiotics. Interestingly, Staphylococcus, the key microbe in the SNI group, influenced Lactobacillus through cooperative interactions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Bulgaricus, L. acidophilus, Streptococcus thermophilus) alleviated chemotherapy-induced neuropathic pain in an in vitro model, but has not been tested yet in vivo [12]. A recent study attempted to use probiotics (i.e., Lactobacillus reuteri lr06 or Bifidobacterium bl5b) to alleviate SNI (spared-nerve injury; a traumatic peripheral nerve injury)-induced neuropathic pain, but failed [42].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies showed that the supplementation of probiotics is effective for combating various pathogens (Ayala et al, 2019;Dean et al, 2019;Piewngam et al, 2018) and reducing anxiety and depression-related behavior in mice (Bravo et al, 2011). Huang et al (2019) attempted to treat neuropathic pain in rats with oral supplementation of probiotics (i.e., Lactobacillus reuteri LR06 or Bi dobacterium BL5b), but failed. Along with the reasons provided by Huang et al (2019), we speculate that the treatment failed because key microbes in the rats with neuropathic pain were in uenced by and cooperated with the probiotics for survival, and these attenuated the analgesic effects of the probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (2019) attempted to treat neuropathic pain in rats with oral supplementation of probiotics (i.e., Lactobacillus reuteri LR06 or Bi dobacterium BL5b), but failed. Along with the reasons provided by Huang et al (2019), we speculate that the treatment failed because key microbes in the rats with neuropathic pain were in uenced by and cooperated with the probiotics for survival, and these attenuated the analgesic effects of the probiotics. Interestingly, Staphylococcus, the key microbe in the SNI group, in uenced Lactobacillus through cooperative interactions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Bulgaricus, L. acidophilus, Streptococcus thermophilus) alleviated chemotherapy-induced neuropathic pain in an in vitro model, but has not been tested yet in vivo (Castelli et al, 2018). A recent study attempted to use probiotics (i.e., Lactobacillus reuteri lr06 or Bi dobacterium bl5b) to alleviate SNI (spared-nerve injury; a traumatic peripheral nerve injury)-induced neuropathic pain, but failed (Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%